Recurring Translocations in Barrett’s Esophageal Adenocarcinoma - Bajpai, Manisha; Panda, Anshuman; Birudaraju, Kristen; Van Gurp, James; Chak, Amitabh; Das, Kiron M.; Javidian, Parisa; Aviv, Hana (Frontiers in Genetics, 2021)
Barrett's esophagus (BE) is a pre-malignant metaplasia in patients with chronic gastroesophageal reflux disease (GERD). BE can progress to esophageal adenocarcinoma (EA) with less than 15% 5yr survival. Chromosomal aneuploidy, deletions and duplication are early events in BE progression to EAC, but reliable diagnostic assays to detect chromosomal markers in premalignant stages of EA arising from BE are lacking. Previously, we investigated chromosomal changes in an in-vitro model of acid and bile exposure induced Barrett’s epithelial carcinogenesis (BEC). In addition to detecting changes already known to occur in BE and EAC, we also reported a novel recurring chromosomal translocation t(10:16) in the BE cells at an earlier time point before they undergo malignant transformation. In this study, we refine the chromosomal event with the help of fluorescent microscopy techniques as a three-way translocation between chromosomes 2, 10 and 16, t(2:10;16) (p22;q22;q22). We also designed an exclusive FISH-EA (Fluorescent In-Situ Hybridization for Esophageal Adenocarcinoma) assay that detects these chromosomal breakpoints and fusions. We validate the feasibility of the FISH-EA assay to objectively detect these chromosome events in primary tissues by confirming the presence of one of the fusions in paraffin-embedded formalin fixed human EA tumors. Clinical validation in a larger cohort of BE progressors (developed EA) and non-progressors ( did not develop EA) will confirm the specificity and sensitivity of the FISH-EA assay in identifying malignant potential in the early stages of EA.